Ponyo sur la falaise : le testament mythopoétique de Hayao Miyazaki - Nathalie Dufayet (Strenae)
Hayao Miyazaki has been the undisputed master of animated fantasy since the mid-1980s and the founding of Studio Ghibli, which he created with director Isao Takahata and producer Toshio Suzuki. His work, which has won numerous international awards over the past 15 years, is undoubtedly one of the finest expressions of modern fantasy, and considered by the mangaka to be continually at the crossroads of writing and rewriting. His art of storytelling is based on the invention of other imaginary worlds, literary intertextuality, the perpetual reinvention of Shinto folklore, and, more broadly, on universal mythic culture. Released in Japan in 2009, the feature film Ponyo, initially intended for young people, would become, in addition to his ultimate faëric masterpiece, the synthesis of his singular vision of fictional invention. Hence its testamentary and metafictional dimensions, which this paper will analyze.